2007
DOI: 10.1002/bip.20905
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transition and liquid crystalline state of regenerated silk fibroin in water

Abstract: The conformational transition of molecular chains of regenerated silk fibroin (SF) aqueous solution is systematically investigated by circular dichroism, Raman, IR, and UV-vis spectroscopies. It is found that an initial random coil conformation of the SF can be readily changed into an ordered beta-sheet structure by optimizing the solution conditions, such as the SF concentration, pH, temperature, or metal-ion content. Circular dichroic spectra quantitatively confirm a steadily decreased content of the random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…In particular, it was demonstrated that in typical silk solution the fluorescence spectrum profile can be attributed to tyrosine, tryptophan and crosslinks emission components which are differently weighted according to the conformational states of silk fibroin, and thus to the different silk forms [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it was demonstrated that in typical silk solution the fluorescence spectrum profile can be attributed to tyrosine, tryptophan and crosslinks emission components which are differently weighted according to the conformational states of silk fibroin, and thus to the different silk forms [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Ultrapure water measured under the same experimental conditions was subtracted from the data. Ellipticity [ θ ] is expressed in units of deg·cm 2 dmol −1 using the Yang equation: true[θtrue] = 78 ×θobs/true(10lctrue) where θ obs is the observed ellipticity value in degrees, the value 78 is the mean residue molecular mass taken from sequence data for SF, l is the optical path length in centimeters, and c is the SF protein concentration in g/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the SF/SS fiber had another two characteristic bands at 1085 cm −1 and 1680 cm −1 . The former was assigned to the ␤-sheet conformation [44,45] and the latter was assigned to the intermediate conformation related to the ␤-sheet. By contrast, for the pure SF fiber, these two bands were exhibited weakly as shoulder peaks.…”
Section: Morphology Of Coaxially Electrospun Sf/ss Fibersmentioning
confidence: 99%